NEO-PETIK LAUT: LOCAL WISDOM IN ENVIRONMENTAL CONSERVATION AND IMPROVEMENT OF COASTAL COMMUNITY ECONOMIC BLUE SPRING MALANG - Haani Arief Muzakki; Mochammad Harits Adi Saputro; Rizky Jakfar Triandi; Nela Maulina Fatikah; Rokhmatin Rokhmatin (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
Petik laut is a tradition routinely done by people around the beach area Sendang Biru for seven days. This tradition is carried out as a form of gratitude to the yields obtained within one year. Most of the crops used as offerings below to sea and drowned. Petik laut is a local wisdom that is ingrained and believed to be a respect for nature. However, it would be better if the culture can work together and in harmony with nature that has provided many benefits. So that local knowledge can provide added value to the environment, particularly the marine environment that will have a positive impact. Therefore, the necessary insertion of several activities in the tradition of sea quotation. Implementation of the activities discussed in this proposal is to transplant coral reefs, Restocking Groupers and clean beach. Hopefully this program can be a benchmark for the success of environment l conservation in the marine waters buadaya integration and local knowledge, as well as an example for the ceremony Pick Sea in all regions in Indonesia. Keywords: value added, coral transplantation, restocking, grouper